Combined surgical techniques in the treatment of hypopigmented scars in discoid lupus erythematosus - Rafael Rezende Rocha de Oliveira; Jade Noleto Viana; Kaique Arriel; Rafael Rubinho; Fernanda Rytenband (Surgical & Cosmetic Dermatology)
Discoid lupus erythematosus (DLE) causes chronic lesions that can heal with dyschromic patches. We report a clinical case showing success in the treatment of achromic lesions using a combination of surgical techniques, including excision, punch grafting, and full-thickness skin grafting.